Vitamin D and atherosclerosis - Olivera Rašević; Maida Mulić; Maja Vuković; Vesna Lazić; Biljana Mijović; Miloš Maksimović (Биомедицинска истраживања, 2021)
Cardiovascular diseases rank first on the mortality list globally or 31%. The basic measure of prevention in accordance with the recommendations of the World Health Organization is a change in risk lifestyle in terms of diet, physical activity, tobacco and alcohol consumption. Vitamin D was previously recognized as a regulator of calcium and phosphorus ratio, bone remodeling or the main controller of skeletal pathophysiology. However, vitamin D enjoys great interest in clinical and epidemiological research in terms of its possible impact on reducing the risk of cardiovascular diseases. Among other things, vitamin D deficiency is associated with an increased risk of endothelial dysfunction. Although the deficiency has been identified as a risk marker for cardiovascular diseases, the mechanism of action of vitamin D on the path from endothelial dysfunction to cardiovascular diseases has not been fully revealed. The findings in this segment of activity of vitamin D would be significant in terms of reducing morbidity and mortality from cardiovascular diseases.
Keywords: vitamin D; endothelial dysfunction; atherosclerosis; cardiovascular diseases; mortality